1979
DOI: 10.1007/bf02906187
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rain on β-glucan content in barley grains

Abstract: The effect of rain on the viscosity of an acid flour extract and on the acid-soluble, acid-insoluble and total ~-glucan contents of barley flour has been investigated. Four commercial varieties and two high lysine genotypes were studied. In the commercial varieties rain induces a decrease in the viscosity of the acid flour extract which is paralleled by decreases in soluble and total ~-glucan contents. Furthermore, it is concluded that the rain did not alter the structural nature of the acid-soluble ~,-glucans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
22
0
1

Year Published

1979
1979
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 12 publications
(8 reference statements)
8
22
0
1
Order By: Relevance
“…This effect is quite clear in Triumph, even when the difference in the drymatter curves is taken into account. The data obtained thus confirm the results reported by AASTRUP (1).…”
Section: Phytotron Studysupporting
confidence: 91%
See 2 more Smart Citations
“…This effect is quite clear in Triumph, even when the difference in the drymatter curves is taken into account. The data obtained thus confirm the results reported by AASTRUP (1).…”
Section: Phytotron Studysupporting
confidence: 91%
“…Minerva and Triumph were grown as single plants in pots on trolleys in the phytotron of the Royal College of Forestry in Stockholm (1,39). The plants were grown on a sterile substrate of fine stones, sand and perlite, nutrient being supplied by watering with dilute Hoagland solution until the plants water requirements were satisfied.…”
Section: Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…dry conditions before harvest have been related with high β-glucan levels (Anderson et al, 2003;Bendelow 1975). Hot and dry climate conditions, early harvesting time and increasing nitrogen rates give rise to increased viscosity of barley extracts, while rain induced a decrease in viscosity which could be related to the lower β-glucan content (Aastrup 1979). …”
Section: Annual Variation Of β-Glucan Contentmentioning
confidence: 99%
“…At full ripeness the total ␤-glucan content for the raintreated plants was significantly lower than in grains from the control plants. In a study of barley grown in field on different locations in Denmark Aastrup 1 found that the extract viscosity was negatively correlated to the precipitation and to relative humidity. These field results confirm that extract viscosity and thus the soluble ␤-glucan content are affected during later stages of ripening by both precipitation and relative humidity.…”
Section: )Jjigxw Hyi Xs Psgexmsr Erh Gpmqeximentioning
confidence: 99%